Self-censorship in journalism / Nurul Asyiqin Nazri Shah…[et.al] - Nazri Shah, Nurul Asyiqin; Rosdi, Nurul Najwa; Jawa, Bryer Tipa; Sapran, Nursyamiera Hanis; Helmy, Nurul Armey Hidayah Helmyzza (Faculty of Communication and Media Studies, 2016)
In this era, there are many ways to conveyor provide information and messages to the public either it is important or not. One of the sender or provider of information and data is the job of the journalist. Basically, journalism is an activity of creating, gathering and presenting news and information to wide viewers or readers. As a journalist, the purpose of journalism is to provide citizens with the information they need in order to make the best possible decisions regarding a certain issue, their communities or even their governments. In details, there are two forms of censorship in the media which are censorship and self-censorship. Censorship occurs when a state, political, religious or private party prohibits information from reaching citizens whereas self-censorship occurs when journalists themselves prevent the publication of information. Hence, this report examines the publics and journalist itself regarding self-censorship in journalism. The purpose of this study was to study and determine the delivering method of censorship information's without crossing the line and exposing information too much. Other than that, the purpose also was to identify the journalists' belief regarding self-censorship. There are 6 purposive participants had answered the researchers' questions about their perceptions on self-censorship in journalism. The data collected indicated that majority of the informants admitted to support and used self-censorship in their writing as a journalist.